2008
DOI: 10.1093/nar/gkn311
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid change in histone H4 enhances UV survival and DNA repair in yeast

Abstract: Single amino acid changes at specific DNA contacts of histones H3 and H4 generate SWI/SNF-independent (Sin) mutants in yeast. We have analyzed the effect of the Sin mutation at R45 of histone H4 on cell survival following UV irradiation, nucleotide excision repair (NER) and chromatin structure. We find that this mutation renders yeast cells more resistant to UV damage and enhances NER at specific chromatin loci. In the transcriptionally silent HML, repressed GAL10 and the constitutively active RPB2 loci, H4 R4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Over the course of repair, the smear returns to a HMW band indicative of repaired, full length DNA. Until now, visualization of the cleavage products has typically been via 32 P labeled probes [59], [61], [62] or ethidium bromide [63], [64]. In Figure 7A, we show an example of mock-infected samples irradiated at 50 J/m 2 and then digested with T4, run on an alkaline agarose gel and stained with SYBR Gold, a ss and dsDNA binding dye, to illustrate these gels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of repair, the smear returns to a HMW band indicative of repaired, full length DNA. Until now, visualization of the cleavage products has typically been via 32 P labeled probes [59], [61], [62] or ethidium bromide [63], [64]. In Figure 7A, we show an example of mock-infected samples irradiated at 50 J/m 2 and then digested with T4, run on an alkaline agarose gel and stained with SYBR Gold, a ss and dsDNA binding dye, to illustrate these gels.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques have been used extensively to study genomic [59], [63], [64] and gene-specific [61], [62] CPD repair in a variety of organisms. However, determining repair of virus and host genomic DNA independently within HCMV-infected cells proved more challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The MNase accessibility was measured as previously described [47]. Briefly, 50 ml cultures of mid-log phase yeast cells (~ 1.0× 10 7 cells/ml) were pelleted, washed with PBS, suspended in yeast lytic enzyme YLE buffer containing10 mg/ml zymolaze (MP Biomedicals) in 1M sorbitol and 5 mM β-mercaptoetanol, and incubated at 30° C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nag et al . reported that the mutation H4R45C increases the accessibility of nucleosome DNA in chromatin to exogenous nucleases and may expedite nucleosomal rearrangements during nucleotide excision repair 15 .…”
mentioning
confidence: 99%